Method Development and Validation for the Simultaneous Determination of Fexofenadine Hydrochloride and Montelukast Sodium in Drug Formulation Using Normal Phase High-Performance Thin-Layer Chromatography. (17th May 2012) - Tandulwadkar, Suparna S.; More, Snehal J.; Rathore, Atul S.; Nikam, Ajinkya R.; Sathiyanarayanan, Lohidasan; Mahadik, Kakasaheb R.
Abstract : A simple, precise, specific, and accurate high-performance thin-layer chromatographic method has been developed for the simultaneous determination of fexofenadine hydrochloride (FEX) and montelukast sodium (MTKT) in pharmaceutical dosage form. The separation was carried out on Merck HPTLC aluminum plates of silica gel G60 F254, (20 × 10 cm) with 250 μm thickness using toluene: ethyl acetate: methanol: ammonia (30%) (0.5: 7: 2: 0.5, v/v/v/v) as mobile phase. HPTLC separation of the two drugs followed by densitometric measurement was carried out in the absorbance mode at 220 nm. The drugs were resolved satisfactorily with R f values of 0.21 ± 0.01 and 0.59 ± 0.01 for FEX and MTKT, respectively. The linear regression analysis data for the calibration plots showed good linear relationship with r 2 = 0.9996 and 0.9998 for FEX and MTKT, respectively, in the concentration range of 2400–10800 ng spot -1 for FEX and 200–900 ng spot -1 for MTKT. The method was validated for precision, robustness, specificity, and accuracy. The limits of detection and quantitation were 100 and 300 ng spot -1, respectively, for FEX and 50 and 100 ng spot -1, respectively, for MTKT. The proposed developed HPTLC method can be applied for identification and quantitative determination of FEX and MTKT in bulk drug and drug formulation.